Sisal fiber reinforced hollow concrete blocks for structural applications: Testing and modeling. (1st October 2017) - Soto Izquierdo, Indara; Soto Izquierdo, Orieta; Ramalho, Marcio Antonio; Taliercio, Alberto
Highlights: Tests on blocks, prisms, and walls made of concrete reinforced with sisal fibers were carried out. The influence of the fibers was pointed out by comparison with tests on plain concrete specimens. Fibers decrease the stiffness of the specimens, but increase their ductility. Fibers decrease the strength of blocks and prisms, but increase the strength of the walls. Finite element models were developed to predict the mechanical behavior of the blocks. Abstract: An experimental programme was carried out to investigate the mechanical behavior of masonry elements made of concrete and natural sisal fibers. Compression tests were carried out on individual hollow blocks, as well as on prisms and wallettes made of hollow blocks. For comparison, the mechanical response of companion plain concrete specimens was also assessed. The results of the tests are presented, and the influence of the sisal fibers on the mechanical properties of the elements is discussed. Numerical models were also developed to predict the nonlinear behavior of the blocks. The parameters and the boundary conditions that define the models are calibrated to match the experimental load-displacement curves. A qualitative description of the damage evolution in the elements using the smeared crack model implemented in the commercial FE program DIANA and the XFEM implemented in Abaqus is obtained. The experimental and numerical results are critically discussed, and possible future improvements of the proposed models are outlined.